The role of local wisdom on green competitive advantages in batik MSMEs: Green innovation as a mediator - Wibowo, Nugroho Mardi; Widiastuti, Yuyun; Tampubolon, Liosten Rianna Roosida Ully; Bramantijo, (International Journal of Management and Sustainability, 2025)
This study examines the influence of local wisdom on green competitive advantage in micro, small, and medium enterprises (MSMEs) within the batik industry in East Java, Indonesia. It also investigates the mediating role of green innovation in linking local wisdom and green competitive advantage. A purposive sampling method was used, resulting in 79 batik MSMEs selected as study objects, with 122 respondents consisting of MSME owners and/or managers. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings show that local wisdom positively influences green product innovation, green process innovation, and green competitive advantage. Notably, green process innovation plays a significant role in enhancing green competitive advantage, while green product innovation does not demonstrate a similar impact. Furthermore, green process innovation mediates the relationship between local wisdom and green competitive advantage, whereas green product innovation does not. The study highlights the importance of integrating local wisdom into sustainable business practices to strengthen competitiveness. It also emphasizes the need for targeted strategies to overcome barriers such as financial limitations, underdeveloped green markets, and limited government support. Enhancing education and training for MSME owners, alongside increasing consumer awareness of green products, should be prioritized for future development.